2001
DOI: 10.1152/jn.2001.85.3.1322
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory Input to Auditory Association Cortex in the Macaque Monkey

Abstract: We investigated the convergence of somatosensory and auditory inputs in within subregions of macaque auditory cortex. Laminar current source density and multiunit activity profiles were sampled with linear array multielectrodes during penetrations of the posterior superior temporal plane in three macaque monkeys. At each recording site, auditory responses to binaural clicks, pure tones, and band-passed noise, all presented by earphones, were compared with somatosensory responses evoked by contralateral median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
286
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(318 citation statements)
references
References 37 publications
28
286
4
Order By: Relevance
“…These recent results were highly complementary to the pioneer works of Schroeder's laboratory that have revealed the multimodal feature of the monkey auditory belt where both visual and somatosensory responses can be evoked (Schroeder et al, 2001;Schroeder and Foxe, 2002;Fu et al, 2003). In the carnivore, while previous studies have reported that the visual cortex can be activated by auditory stimuli (Spinelli et al, 1968;Morrell, 1972;Fishman and Michael, 1973), intracellular recording in the primary visual cortex (A17) have recently failed to find such auditory responses (Sanchez-Vives et al, 2006).…”
Section: Electrophysiological Evidence In the Primary Sensory Areassupporting
confidence: 66%
See 2 more Smart Citations
“…These recent results were highly complementary to the pioneer works of Schroeder's laboratory that have revealed the multimodal feature of the monkey auditory belt where both visual and somatosensory responses can be evoked (Schroeder et al, 2001;Schroeder and Foxe, 2002;Fu et al, 2003). In the carnivore, while previous studies have reported that the visual cortex can be activated by auditory stimuli (Spinelli et al, 1968;Morrell, 1972;Fishman and Michael, 1973), intracellular recording in the primary visual cortex (A17) have recently failed to find such auditory responses (Sanchez-Vives et al, 2006).…”
Section: Electrophysiological Evidence In the Primary Sensory Areassupporting
confidence: 66%
“…Although somewhat surprising, there is evidence for the existence of multisensory neurons in areas traditionally considered as unisensory, such as the visual cortex (between areas 17 and 18a) in the rat (Barth et al, 1995) and in the auditory cortex of the monkey (Watanabe and Iwai, 1991;Schroeder et al, 2001;Cappe et al, 2007b;Kayser et al, 2008) and of the ferret (Bizley et al, 2007;Bizley and King, 2008). In addition, previous studies have shown the existence of scattered projections of the auditory cortex towards the visual area 18 in the rat and the cat (Miller and Vogt, 1984;Innocenti et al, 1988).…”
Section: Primary Sensory Areas Receive Non-specific Inputsmentioning
confidence: 98%
See 1 more Smart Citation
“…The hypothetical mechanism underlying a putative protective function may relate to the fact that the playing of an instrument generates regularly patterned and correlated reafferent input streams to the auditory and the somatosensory system. There are multiple somatosensory entries into the auditory system that are capable of modulating auditory cortex activity (Schroeder et al, 2001; Lakatos et al, 2007). Increase of auditory cortex size and enhancement of fiber projections through the anterior CC may represent components of a protective auditory-motor-somatosensory-auditory loop.…”
Section: Discussionmentioning
confidence: 99%
“…Given the extant literature on multisensory integration, a cross-modal sensory gating effect was not unexpected here. For example, the presence of both anatomical substrates (Schroeder et al, 2001) and functional interactions (Brett-Green et al, 2004;Foxe et al, 2002) between auditory and somatosensory modalities has been demonstrated at the cortical level. The latter includes scalp-recorded neurophysiological effects on the same time-scale (<100 ms) as that observed here (Foxe et al, 2000;Murray et al, 2005).…”
Section: Sensory Gating Across Modalitiesmentioning
confidence: 99%